2019
DOI: 10.1007/s10162-019-00714-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone Methyltransferase G9a Attenuates Noise-Induced Cochlear Synaptopathy and Hearing Loss

Abstract: Posttranslational modification of histones alters their interaction with DNA and nuclear proteins, influencing gene expression and cell fate. In this study, we investigated the effect of G9a (KMT1C, EHMT2), a major histone lysine methyltransferase encoded by the human EHMT2 gene and responsible for histone H3 lysine 9 dimethylation (H3K9me2) on noiseinduced permanent hearing loss (NIHL) in adult CBA/J mice. The conditions of noise exposure used in this study led to losses of cochlear synapses and outer hair ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…A previous study by our research group reported that neomycin-induced elevations of histone methyltransferase G9a and H3K9me2 amounts are associated with aminoglycoside-induced hair cell loss, and pharmacological targeting of G9a with BIX 01294 could prevent damage to inner ear hair cells (Yu et al 2013). Delivery of G9a siRNA in vivo 72 h prior to noise exposure also significantly reduced ABR threshold shifts and ameliorated noise-induced permanent hearing loss (Xiong et al 2019). Additionally, a histone deacetylase inhibitor, suberoylanilide hydroxamic acid, was shown to protect outer hair cells from noise-induced damage, hence, raising the possibility that epigenetic regulation may be a potential therapeutic strategy to prevent hearing loss (Wen et al 2015).…”
Section: Discussionmentioning
confidence: 69%
“…A previous study by our research group reported that neomycin-induced elevations of histone methyltransferase G9a and H3K9me2 amounts are associated with aminoglycoside-induced hair cell loss, and pharmacological targeting of G9a with BIX 01294 could prevent damage to inner ear hair cells (Yu et al 2013). Delivery of G9a siRNA in vivo 72 h prior to noise exposure also significantly reduced ABR threshold shifts and ameliorated noise-induced permanent hearing loss (Xiong et al 2019). Additionally, a histone deacetylase inhibitor, suberoylanilide hydroxamic acid, was shown to protect outer hair cells from noise-induced damage, hence, raising the possibility that epigenetic regulation may be a potential therapeutic strategy to prevent hearing loss (Wen et al 2015).…”
Section: Discussionmentioning
confidence: 69%
“…However, exposure to 100 dB SPL for 2 h induces PTS with losses of both OHCs and IHCs in a fashion similar to that of exposure to 106 dB SPL in the same strain of mice at the age of 12 weeks [13,36,42]. Additionally, we were unable to induce PTS with loss of OHCs only (non IHC loss) when using 8-week-old CBA/J mice without dietary enrichments, although we have previously characterized such noise conditions with same strain mice at the age of 12 weeks [51,53]. Regardless of whether octave band (with a frequency spectrum from 8–16 kHz) or broadband noise exposure (with a frequency spectrum from 2–20 kHz) is used with mice at either age (8 or 12 weeks), noise-induced loss of sensory hair cells follows a base-to-apex gradient beginning in the basal turn [13,51,54].…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of or protection against hearing loss, a number of different RNAi strategies differing in RNA targets, delivery modalities, and types of siRNA/miRNA molecules have shown efficacy in animal models. These include but are not limited to RNA approaches involving the knockdown of mRNA encoding toxic, gain-of-function proteins [26,43] or modulation of gene pathways that limit regeneration or protect against noise-induced hearing loss [44][45][46] or cisplatin-induced ototoxicity [47][48][49]. In most cases reported, unformulated siRNAs were delivered via trans-tympanic injection to the middle ear prior to the induction of hearing and hair cell damage, which results in modest protection from hearing loss.…”
Section: Rna Interferencementioning
confidence: 99%